Torujac droge teorii lingwochronologizacji - Wierzchoń, Piotr (Investigationes Linguisticae, 2010)
A theory of linguochronologization (TLCH) is outlined and offered for consideration. Linguochronology as a subdiscipline of applied linguistics is composed of a theoretical and a practical part. This latter could be termed linguochronography. The subject matter of TLCH is textual reality, that is, the reality comprised of all texts ever produced by the users of any given ethnic language, in this case Polish (the texts of which have been obtained from the dLibra system devised by the Poznan Supercomputing and Networking Center). The theory proposed here is particularly oriented towards the chronologization of units of language (types) via a datation operation of the textual objects (tokens) by which these units are represented. Within TLCH the following components are distinguishable: (i) primitive terms, (ii) postulates (axioms), (iii) directives, (iv) photodocumentation. The primitive terms include: units of language, textual objects, textual dimensions (parameters), and others. By means of the postulates, textual objects are characterized with respect to textual dimensions. The directives secure the application of effective procedures for a linguochronographic enterprise. One of these procedures is just photodocumentation which enhances the reliability of the inquiry into graphic properties of printed texts including both their spelling and typography and at the same time serving as a confirmation procedure. Subsequently some theoretical and practical problems of linguochronologization are submitted for discussion inspired by Prof. Krystyna Waszakowa’s paper (2010), which abounds in penetrating and critical observations and foreshadows, at long last, the beginning of a pertinent debate concerning TLCH.